Monitoring System of Functional Ability of University Students in the Process of Physical Education - Ivan Samokish; Anatoly Bosenko; Oleksandr Pryimakov; Viktoriya Biletskaya (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
Given research is devoted to the regional criteria development for evaluation of educational achievements and preparation of practical recommendations for teachers of higher educational institutions on the application of methodology for assessing the functional opportunities in process of physical education. During the research evaluation standards of functional opportunities of students were developed with the usage of mathematical statistics on the basis of the average arithmetic value (M) and standard deviation (σ). The study involved 150 students (86 girls and 64 boys, who belonged to the main medical group).Appropriate norms provide more complete information about positive (negative) changes of functional opportunities’ level compared with traditional pedagogical tests. There are represented practical recommendations on the usage of functional testing during training sessions at universities in order to optimize the process of physical education.